Effect of contact angle on meniscus evolution and contact line jump of underfill fluid flow in flip-chip encapsulation - Ng F.C.; Tung L.H.; Zawawi M.H.; Mukhtar M.A.F.M.; Abas M.A.; Abdullah M.Z. (Penerbit Akademia Baru, 2023)
Despite the contact angle of underfill fluid is largely correlated to the flowability, it was scarcely being investigated in the design optimization of flip-chip underfill encapsulation process. Furthermore, the detailed implication of the variation of contact angle on the flow mechanism was never being discussed. Thus, this paper is devoted to study the variation effect of contact angle on both spatial aspects of meniscus evolution and contact line jump of underfill flow menisci. The governing analytical equations that describe both meniscus evolution and contact line jump were well-validated with the past experimental and numerical findings. It was revealed that the bump contact angle critically determined the separation between concave and convex menisci. Generally, larger bump contact angle yields the earlier formation of convex menisci that is nearer to the bump entrant. Consequently, the occurrence of convex menisci in the bump region increased for the case of high bump contact angle. Moreover, when the contact angle increases, the equilibrium positions of entrant jump meniscus locates nearer to the bump entrant; while the equilibrium meniscus of exit jump becomes further away from the bump exit. These findings provided microscopic insights of the influence of contact angle on the characteristic and dynamic of flow menisci upon interacting with the solder bump array, which may benefit both electronic packaging and microfluidics sectors in general. 2020 PENERBIT AKADEMIA BARU-All rights reserved.